2023
DOI: 10.1021/acscatal.2c05081
|View full text |Cite
|
Sign up to set email alerts
|

Efficiently Light-Driven Nonoxidative Coupling of Methane on Ag/NaTaO3: A Case for Molecular-Level Understanding of the Coupling Mechanism

Abstract: Metal-decorated oxide semiconductors are overwhelming photocatalysts for nonoxidative coupling of methane (NOCM). However, the overall NOCM mechanism remains an unopened black box, which hinders the design of high-performance catalysts. Herein, we systematically studied a series of noble metal (Ag, Au, Pt, Pd, Cu, and Ni)-decorated oxides (NaTaO3, CaTiO3, LiNbO3, and TiO2) for NOCM. We proposed that the active sites for H abstraction and C–C coupling of CH4 are spatially separated. Specifically, NaTaO3 only co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 65 publications
1
23
0
Order By: Relevance
“…These results clearly demonstrated that the decrease of the activity on 1.5 Ag 3 PO 4 -ZnO may be caused by the reduction of Ag + , and then remained stable when the Ag NPs and Ag 3 PO 4 -ZnO form a stable heterojunction. According to a previous study, the Ag NPs favor the desorption of *CH 3 , so the formation of Ag NPs prevents the excessive oxidation of *CH 3 and improves the selectivity of C 2 H 6 and C 2 –C 3 hydrocarbon production …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…These results clearly demonstrated that the decrease of the activity on 1.5 Ag 3 PO 4 -ZnO may be caused by the reduction of Ag + , and then remained stable when the Ag NPs and Ag 3 PO 4 -ZnO form a stable heterojunction. According to a previous study, the Ag NPs favor the desorption of *CH 3 , so the formation of Ag NPs prevents the excessive oxidation of *CH 3 and improves the selectivity of C 2 H 6 and C 2 –C 3 hydrocarbon production …”
Section: Resultsmentioning
confidence: 90%
“…According to a previous study, the Ag NPs favor the desorption of *CH 3 , so the formation of Ag NPs prevents the excessive oxidation of *CH 3 and improves the selectivity of C 2 H 6 and C 2 −C 3 hydrocarbon production. 34 Study of the Process Mechanism. To investigate the charge separation efficiency of the photocatalysts, TPC, EIS, and steady-state PL tests were carried out.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To further confirm the reaction mechanism, we collected in situ DRIFTS spectra to investigate the reaction pathways occurring on the different samples during the hydrogenation of carbon-13 labelled carbon dioxide ( 13 CO 2 ) (Figure 4c). The relative intensity of the peaks observed at 3012 cm À 1 (Figure 4a) and 3002 cm À 1 (Figure 4c) corresponding to 12 CH 4 and 13 CH 4 , respectively suggest that over the Co/ MAO catalyst after the introduction of light, CH 4 was predominantly formed from CO 2 . In addition, in the spectra collected immediately on the CoÀ CoO x /MAO after light irradiation, the positions of the * 13 CO peaks observed at 2146 and 2034 cm À 1 were significantly different from that of the * 12 CO peak (Figure 4b).…”
Section: Forschungsartikelmentioning
confidence: 96%
“…More importantly, the different electron distribution and valence state of two different metal active sites at the interface may cause the charge distribution of the C 1 intermediate to be significantly different, thus reducing the C 1 electrostatic repulsion, promoting the C−C coupling reaction. In addition, the active sites on the interface can be proposed to overcome the long‐distance migration of C 1 intermediates on the asymmetric active sites [13] . Therefore, the construction of charge asymmetric active sites at the interface of two‐phase catalysts has great potential in the CO 2 reduction reaction used to form C 2+ hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation